THE MORPHOLOGICAL AND MORPHOMETRICAL STATE OF THE LIVER IN OFFSPRING BORN TO MOTHERS WITH CHRONIC TOXIC HEPATITIS UNDER CONDITIONS OF MEDICATION CORRECTION BEFORE PREGNANCY (experimental study) - Maloxat B. Nazarova,; Dilorom B. Adilbekova,; Abdulaziz A. Akhrorov,; Sardorjon S. Toshpulatov,; Farangiz O. Rustamova, (Central Asian Journal of Medicine, 2025)
Chronic toxic hepatitis in mothers, when corrected with medication during the pre-pregnancy period, has a positive impact on the morphofunctional state of the liver in both the mother and her offspring. This leads to a reduction in inflammatory-reactive and dystrophic processes, and under conditions of recovery and regeneration, the zones of liver parenchyma damage in both the mother and offspring are significantly reduced. As a result, this contributes to the early elimination of pathomorphological changes in the vascular-tissue structures of the liver in both the mother and offspring. Preventing morphofunctional disorders in the liver of mothers and their offspring, predicting diseases in children born to mothers with liver pathologies, and developing effective methods for early diagnosis and treatment can enhance the resistance of the offspring to various harmful external and internal environmental factors.